Biologically Active Principles of the Seer Fish Scomberomorus commerson Lacepede 1800 Epidermal Mucus - Prithiviraj, N (International Journal of Pharmaceutical & Biological Archive, 2012)
Biologically Active Principles of the Seer Fish Scomberomorus commerson Lacepede 1800 Epidermal Mucus